Family Foundations of Leadership: Perceived Parental Support, Birth Order and Emerging Leadership Qualities - Ãskaree, Dr. Leenah; Haq, Shajeea; Nasir, Muneeza; Khudain, Syed; Sheikh, Alishba (ACADEMIA International Journal for Social Sciences, 2025)
This study investigated the role of perceived parental support and birth order in shaping emerging leadership qualities, situating the inquiry within ecological and developmental frameworks of human growth (Bronfenbrenner & Morris, 2006; Murphy & Johnson, 2011). Using a sample of 163 participants, the research employed correlational and regression analyses to examine both overall and birth-order-specific associations. Across the full sample, perceived parental support was positively and significantly correlated with emerging parental leadership qualities, r(163) = .28, p < .01 (Table 8). Regression analysis confirmed that support significantly predicted leadership qualities, accounting for 7.8% of the variance, R² = .078, F(1, 161) = 13.54, p < .001 (Tables 9–11). The regression coefficient was significant, B = 0.25, β = .28, t(161) = 3.68, p < .001, with a 95% CI [0.11, 0.38], indicating that higher levels of parental support were associated with stronger leadership qualities. Birth-order analyses revealed important subgroup differences. Among first-borns, the correlation between parental support and leadership qualities was weak and non-significant, r(51) = .13, p = .357 (Table 13), suggesting that their leadership development may be shaped more by structural family roles than by perceived support (Sulloway, 1996). In contrast, second-borns demonstrated a strong and significant association, r(34) = .62, p < .001 (Table 14), highlighting the critical role of parental encouragement in fostering their leadership potential. Middle-borns (r(47) = .23, p = .118; Table 15) and last-borns (r(31) = .24, p = .195; Table 16) showed modest, non-significant correlations, suggesting that their leadership qualities may be more strongly influenced by external contexts such as peer networks and educational opportunities (Salmon & Daly, 1998). Overall, the findings confirm that perceived parental support is a meaningful predictor of leadership qualities, but its strength varies systematically by birth order. These results contribute to leadership development research by demonstrating that family dynamics moderate the influence of parental support on leadership emergence, reinforcing the view that leadership is a developmental outcome shaped by the interplay of family, individual, and contextual factors (Day & Dragoni, 2015). Future research should employ longitudinal and cross-cultural designs to further clarify these dynamics and to explore how family-based influences interact with broader social and organizational contexts in cultivating leadership across the lifespan.